Implementing Religious Moderation as a Strategy for Anti-Discrimination Education in Islamic School Management - Memo Valentino Hutagaol; Zainal Arifin; Anip Dwi Saputro; Mohammad Muslih; Syamsul Arifin (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
The rising incidents of violence and discrimination under the guise of religion in Indonesian society emphasize the need for effective educational strategies to foster social harmony. This study investigates the implementation of religious moderation as a strategy for anti-discrimination education in Islamic school management, with a focus on SMAN 1 Ponorogo. Using a qualitative field research approach, data were collected through observations, interviews, and document analysis and analyzed using the Miles and Huberman model. The findings reveal that religious moderation, rooted in the concept of “wasathiyah” (balance), serves as a critical framework for nurturing tolerance, empathy, and respect among students of diverse religious and ethnic backgrounds. The school’s management plays a pivotal role in sustaining these values through strategic policies, including curriculum integration, multicultural education, teacher training, and clinical supervision. Student testimonies and teacher reflections illustrate the tangible impact of these initiatives, with students developing emotional resilience and forming close bonds across religious lines. The research highlights that religious moderation not only enhances school harmony but also has broader societal implications, acting as a preventive measure against radicalism and contributing to national unity. The study underscores the need for continued policy support, community engagement, and ongoing professional development to ensure the long-term sustainability of religious moderation as a cornerstone of peace education in Indonesia.